Pattern of Substance Abuse among Professional Drivers and Job Seekers in Bangladesh (Journal of Monno Medical College, 2025)
Background: Drug abuse is a significant public health concern in Bangladesh, particularly among vulnerable populations such as professional drivers and job seekers. The high mobility and stress associated with these occupations may contribute to increased substance use, affecting their health, safety, and productivity.Objective: This objective of the study to assess the prevalence of drug abuse among professional drivers and job seekers in Bangladesh and identify associated factors influencing substance use patterns in these groups.Methodology:  This cross-sectional study was conducted at the Department of Biochemistry at National Institute of Laboratory Medicine & Referral Centre (NILMRC), Dhaka, Bangladesh from July 2022 to December 2022. Urine samples (n = 91,745) were collected from professional drivers and job seekers and screened for drug metabolites using 5-panel rapid test cassettes. Positive samples were further analyzed quantitatively.Results: Among the positive cases, 3% tested positive for drug abuse. The most commonly detected substance was cannabinoids (90.89%), followed by benzodiazepines (5.8%), amphetamines (1.35%), opiates (1.13%), and alcohol (0.8%). Drug use was most prevalent in individuals aged 25-34 years (35.62%), followed by those aged 35-44 years (34%). A strong correlation was observed between drug use and gender, with 99.93% of positive cases being male. Significant associations were found between drug use and both age and gender (p < 0.05).Conclusion: This study underscores the high prevalence of cannabinoid use among younger male drivers in Bangladesh, highlighting the need for targeted interventions to reduce drug abuse and enhance road safety. Future research should investigate underlying causes and prevention strategies.Journal of Monno Medical College December, 2024;10 (2):55-60